The relationship between income and nutritional status with the incidence of hypertension in elderly - Sariyanti, Emi Nur; Hanim, Diffah; Anantanyu, Sapja (International Journal of Human and Health Sciences (IJHHS), 2020)
Background:Blood pressure is a disease that is often found in the elderly. Many studies show that socioeconomic status is closely related to the incidence of hypertension especially in the elderly. In addition, since hypertension is generally associated with being overweight and obese, nutritional status can also be a factor for experiencing hypertension in the elderly. Objective:To analyze the relationship between income and nutritional status with the incidence of hypertension in the elderly. Method: This study used a cross-sectional study design involving 133 elderly respondents in the area of the Klaten Community Health Center. Income data were obtained using the respondents’ basic characteristic questionnaire. Nutritional status was obtained based on anthropometric measurements of body weight and height which were calculated using the Body Mass Index (BMI). While blood pressure data were obtained from Sphygmomanometer measurements. The data obtained were analyzed using the Spearman test with a p-value <0.05. This study was approved by Ethics Commission UniversitasSebelasMaret. Results: The results of this study indicate there is a relationship between income and the incidence of hypertension in the elderly (p=0.046) while the nutritional status has no relationship with the incidence of hypertension (p=0.640). Conclusion: High income has a low risk of the elderly experiencing hypertension, while nutritional status good or not they do not have a risk of hypertension. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 81-84